Efficient One‐Pot Synthesis of Tetrahydronaphtho[2, 1‐f]isoquinolines by Using Domino Pictet–Spengler/Friedel–Crafts‐Type Reactions. Issue 43 (22nd November 2017) - Khunnawutmanotham, Nisachon; Sahakitpichan, Poolsak; Chimnoi, Nitirat; Techasakul, Supanna
Abstract : This study describes a facile and efficient one‐pot method for the synthesis of a tetrahydronaphtho[2, 1‐ f ]isoquinoline alkaloid. An N ‐protected amino aldehyde biaryl substrate underwent domino Pictet–Spengler/Friedel–Crafts‐type cyclization reactions to produce the tetrahydronaphtho[2, 1‐ f ]isoquinoline skeleton. Litebamine, a naturally occurring compound, was prepared by using the proposed approach to exemplify its utility. Abstract : A facile and efficient one‐pot method for the synthesis of a tetrahydronaphtho[2, 1‐ f ]isoquinoline alkaloid by using domino Pictet–Spengler/Friedel–Crafts‐type cyclization reactions has been reported. Litebamine, a naturally occurring compound, was prepared by using this proposed approach to exemplify its utility.